Tirzepatide ameliorates spatial learning and memory impairment through modulation of aberrant insulin resistance and inflammation response in diabetic rats - Guo, Xiying; Lei, Min; Zhao, Jiangyan; Wu, Min; Ren, Zhanhong; Yang, Xiaosong; Ouyang, Changhan; Liu, Xiufen; Liu, Chao; Chen, Qingjie (Frontiers in Pharmacology, 2023)
Background: One of the typical symptoms of diabetes mellitus patients was memory impairment, which was followed by gradual cognitive deterioration and for which there is no efficient treatment.The anti-diabetic incretin hormones glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide-1 (GLP-1) were demonstrated to have highly neuroprotective benefits in animal models of AD. We wanted to find out how the GLP-1/GIP dual agonist tirzepatide affected diabetes's impairment of spatial learning memory.Methods: High fat diet and streptozotocin injection-induced diabetic rats were injected intraperitoneally with Tirzepatide (1.35 mg/kg) once a week. The protective effects were assessed using the Morris water maze test, immunofluorescence, and western blot analysis. Golgi staining was adopted for quantified dendritic spines.Results: Tirzepatide significantly improved impaired glucose tolerance, fasting blood glucose level, and insulin level in diabetic rats. Then, tirzepatide dramatically alleviated spatial learning and memory impairment, inhibited Aβ accumulation, prevented structural damage, boosted the synthesis of synaptic proteins and increased dendritic spines formation in diabetic hippocampus. Furthermore, some aberrant changes in signal molecules concerning inflammation signaling pathways were normalized after tirzepatide treatment in diabetic rats. Finally, PI3K/Akt/GSK3β signaling pathway was restored by tirzepatide.Conclusions: Tirzepatide obviously exerts a protective effect against spatial learning and memory impairment, potentially through regulating abnormal insulin resistance and inflammatory responses.